Killing Mother Natures: Maternity and Womanhood as a Death Sentence in Frankenstein - Mendonca, Alyssa (Spectrum, 2023)
Mary Shelley’s Frankenstein, published in 1818, features only a few women throughout the text who are either removed from the direct action, positioned as observers, or are dead and therefore haunt the text at critical moments. Despite being mostly centered on male characters, Shelley’s text manages to depict the fatality of womanhood under patriarchy. Through Elizabeth, she offers the ‘domestic angel’ trope as one of imprisonment and execution; through the female Creature, marriage as a death trap; through Mother Nature, an account of men’s physical and ideological assaults on women’s bodies; finally, through Mrs. Saville as the novel’s recipient, a woman in a position of power. Through Victor, the image of maternity as punishment is developed, suggesting that the socialization of women as ‘happy’ mothers incinerates female agency and personhood. I argue that inclusion of female deaths in the contexts of marriage and reproduction capitulates patriarchy as a murderous regime whose demands of heteronormative conformity both create and destroy women. I add that Shelley locates the terrors of parturition on male bodies, including a fear of death-by-birth and disgust for one’s child, making legible the reality of tormented, unwilling mothers that is otherwise repressed by patriarchal society. Thus, appropriating male privilege for her purpose, Shelley’s Frankenstein is a novel expressing discontent towards normative institutions, inundating readers who are societally attuned to men’s concerns with feminist coded critiques of the family, marriage, and reproduction.